Analytical Description of the Diffusion in a Cellular Automaton with the Margolus Neighbourhood in Terms of the Two-Dimensional Markov Chain; Mathematics; Vol. 11, iss. 3 - Kulagin A. E. Anton Evgenievich (2023, 2023)
Title screen